PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WONDERSHARE FILMORA PADA MATA PELAJARAN TRANSMISI TENAGA LISTRIK KELAS X TJTL DI SMKN 1 PERCUT SEI TUAN - Anjas Pratama Sinaga; Baharuddin . (Universitas Negeri Medan, 2023)
Abstract The problem in this study is that the existence of media in schools is less practical and difficult to carry and students tend to be able to because teachers explain theoretically and do not optimize technology in media. Wondershare Filmora9-based interactive learning media has never been used by teachers. The objectives of this study are (1) to determine the design process of learning media development wondershare Filmora 9 in the subject of Electric Power Transmission, (2) to determine the feasibility of learning media used in the learning process. The research model used in this study consists of Analysis, design, development, implementation, evaluation (ADDIE). The subjects of this study were students of class XI TJT SMKN 1 Percut Sei Tuan, while the validators of media assessment were UNIMED lecturers and homeroom teachers of class XI TJTL to assess the material and media. The results of this study show that interactive learning media based on Filmora 9 is classified as